Pengembangan Bahan Ajar Pendidikan Karakter Berbasis Cerita Rakyat Etnik Lembak - Agung Nugroho; Inda Puspita Sari; Cekman (CV. Creative Tugu Pena, 2026)
This study aims to develop character education teaching materials based on Lembak ethnic folklore. The research employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, questionnaires, and user feedback. The evaluation process included product testing and assessments by students, practitioners, traditional leaders, and users of the developed materials. The findings identified 14 folktales (sagas) originating from Lembak regions, including Padang Ulak Tanding, Lubuklinggau, Musi Rawas, Musi Banyuasin, Lebong, and North Musi Rawas. Through analysis using a sociological literary approach, 17 out of 18 character education values were identified, supported by 260 relevant excerpts. The needs analysis—covering curriculum, teaching resources, student characteristics, and learning processes—indicated a strong demand for character education materials among both educators and students. Validation results from practitioners showed that the product was rated as excellent in terms of language, instructional content, media design, and cultural relevance. In conclusion, the Lembak ethnic-based character education materials are well aligned with the needs of both students and educators. This study contributes to students, practitioners, cultural observers, readers, and the wider community by promoting local literature as an effective medium for character education in both school and social contexts.